Aspects of tradition - Poljak Istenič, Saša (Traditiones (Ljubljana), 2012)
In ethnology and anthropology, the term tradition usually denotes transmission over time and continuity of phenomena, while recent views also highlight other aspects. Because of disappearance of "typical" cultural phenomena it became a value. Since it has connected people on many levels, it can be perceived as a means of identity politics. At the same time it becomes a strategy to strengthen a sense of belonging and achieve diverse goals. These aspects are presented with some empirical examples.
Keywords: ethnology; Etnologija; Kulturna antropologija; methodology; Kulturna dediščina; cultural heritage; tourism; Narodna identiteta; Turizem; tradicija; tradition; Slovenia; Slovenija